PEMILIHAN MODEL IMPLEMENTASI SPIN-OFF UNIT USAHA ASURANSI SYARIAH DI INDONESIA DENGAN MODEL AHP - Erny Arianty; Abdul Ghoni (Jurnal Ilmiah Ekonomi Islam, 2023)
ABSTRACT This study aims to analyze the factors and spin-off models that have the highest level of importance in realizing the implementation of the Sharia Insurance Business Unit spin-off. This research method uses a qualitative method with an Analytical Hierarchy Process (AHP) approach with key informants from the government, regulators, the sharia insurance industry, AASI, and the Sharia Supervisory Board. The results of this study external factors with government and regulatory support subcriteria have the highest level of importance. For the sub-criteria for internal factors, the leadership support factor has the highest level of importance. The acquisition spin-off model has the highest importance. The implication of this research is the industry should meet the availability of resources so that the spin-off runs smoothly and determines the right spin-off model. For the government, the results of this research can provide an effort to facilitate the spin-off process in the form of policies. Keywords: Spin-Off, Factors, Model, AHP